(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Background: Risk factors for PICC CLABSI (peripherally inserted central venous catheter/ central line associated bloodstream infections) have been evaluated in a limited number of prospective and retrospective studies with conflicting results. Methods: A six year retrospective review of PICC CLABSI within a single institution was performed. PICC CLABSI cases were matched to uninfected controls and host and device data were extracted from comprehensive medical record reviews. A statistical analysis of PICC CLABSI risk factors compared to matched controls was performed. Results: 6756 patients had a PICC line placed during the study period (January 1, 2008 - December 31, 2013). Fifty-six (0.83%) CLABSI were identified and matched to 245 uninfected controls. Factors associated with PICC CLABSI included: sepsis (P<0.0001), history of smoking (P=0.002), hyperlipidemia (P=0.048), duration of PICC (P<0.0001), area of insertion (P=0.019), use of de-clotting agents ( P=0.0009), complication after PICC line insertion (P=0.0008), and use of anti-MRSA antibiotics after PICC insertion ( P=0.006). In multivariant analysis, there was a significant association between PICC CLABSI and sepsis (OR=4.9, CI 2.2-11.1), history of smoking (OR=2.9, CI 1.3 – 6.2) and gastrostomy (OR =6.5, CI 2.2 – 19.4). Conclusions: Risk factors for PICC CLABSI in an institution with low rates of infection include both host factors (sepsis, smoking, gastrostomy tube) and device factors (area of insertion, complications, use of de-clotting agents, anti-MRSA antibiotics after PICC placement, and PICC duration). Preventative measures targeting modifiable risk factors may decrease rates of PICC CLABSI in the future.